Introduction to soil chemistry : analysis and instrumentation - Conklin, Alfred R., Jr. (Alfred Russel), 1941- (Chemical analysis., 2013)
Provides the tools needed to explore the incredible complexities of the earth's soils Now in its Second Edition, this highly acclaimed text fully equips readers with the skills and knowledge needed to analyze soil and correctly interpret the results. Due to the highly complex nature of soil, the author carefully explains why unusual results are routinely obtained during soil analyses, including the occurrence of methane in soil under oxidative conditions. The text also assists readers in developing their own analytical techniques in order to analyze particular samples or test for particular compounds or properties.